Sexual Illusion Of Nina in Black Swan Movie Directed By Darren Aronofsky (2010) : A Behaviorist Perspective - NISWAH, ANITA HARISATUN (2012)
The study gives focus on Behaviourist Perspective as reflected in Darren Aronofsky'sBlack Swan. The study investigates how the sexual illusion influences the personality development of Nina in Darren Aronofsky'sBlack Swanspecially viewed from behaviorist perspective. In this research the writer employs the qualitative method. The object of the research is the movie entitled Black Swan by Darren Aronofsky.In this method,the writer uses two data sources, namely primary data and secondary data sources. Theprimary data source is the movie itself. The secondary data sources include references and materials related to the study picking up from the books or internet. The method of data collection is literary research anddocumentation meanwhilethe technique of data collection is descriptive technique. The result of the study reveals the sexual illusion of Nina who gets some influences from her new environment and job/position. Black Swan represents Darren Aronofsky's response to the role of environment in influencing and shaping someone's behavior.